Analysis of Health Level of Banking Camel Method in Bank Tabungan Pensiunan Nasional (btpn) Sharia 2016-2020 - Ersa Lailatul Silvia; Muhammad Iqbal Pratikto (Universitas Islam Lamongan, 2022)
Assesment of the soundness of financial institution banking is an essential matter. It is used to gain and people trust to islamic ban. The level of capability is the expertise of a bank in doing its operational activity and being able to fullfill its obligations, especially in short-term debt. CAMEL method is used to pay attention to the soundnes level fluctuation of sariah bank by seeing these five types, capital, asset, management, profitability, and liquidity. The result finding indicates that the BTPN Syariah can be categorized as healty banking since 2016-2020. It means during that time period , BTPN Syariah is able to provide guarantees for each deposit which is given to the customer and can pay all of its obligations.